Procurement process and management at horticultural enterprises - Villányi, Réka (The Hungarian Journal of Marketing and Management, 2019)
In the present economic environment even the small cost improvement can give significant competition advantage for companies. The leading companies have realise this, their managers and leaders pay special attention to procurement which can have a positive influence really fast on the result and increase the value and competitiveness of the enterprise. My aim is to reveal the faults and deficiencies in the procurement process in the scope of the enterprises of a branch whose procurement activity is based on careful and premeditated strategy and bound to strive rules. This branch is the vegetable and fruit processing branch where the basic materials are fast deteriorating horticultural products and their procurement management is predetermined.